Enhancement Risk Disease Cardiovascular in Children with Hypospadias - Putra, Aulia Wiratama; Prayuda, Yoga Eka; Suherman, Levita Dyah Kartika; Ratu, Tiffani; Cahyono, Ari Harto (International Journal of Public Health Excellence (IJPHE), 2023)
Hypospadias is a congenital disorder in boys due to low fetal androgen hormones. Hypospadias is one of the congenital disorders with the highest prevalence. Several studies have revealed the association of hypospadias with cardiovascular disease. There are still very few studies that summarize cardiovascular manifestations in pediatric hypospadias. Therefore, this study was designed to describe the cardiovascular risk in pediatric patients with hypospadias. Method : Journal searches were carried out through several research databases including Google Scholar, PubMed, and Sciencedirect . The keywords used were "hypospadias", "cardiovascular", and "pediatric". The results of the literature search were 1,543 journals with 20 journals meeting the criteria. Results and Discussion : Hypospadias is one of the second most common congenital abnormalities in men after testicular undescensus . Children born with hypospadias are proven to experience changes in vascular structure, namely increased carotid intima media thickness (CMIT) and are associated with hypertension. Hypospadias patients have impaired endothelial function, decreased vasorelaxation, and increased vasoreactivity. The underlying mechanism is a Rho kinase and ROS dependent process. Conclusion: Children with hypospadias have a higher risk of cardiovascular disease.